If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 0.6(10 + n) 15 = (10 * 0.6 + n * 0.6) 15 = (6 + 0.6n) Solving 15 = 6 + 0.6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-0.6n' to each side of the equation. 15 + -0.6n = 6 + 0.6n + -0.6n Combine like terms: 0.6n + -0.6n = 0.0 15 + -0.6n = 6 + 0.0 15 + -0.6n = 6 Add '-15' to each side of the equation. 15 + -15 + -0.6n = 6 + -15 Combine like terms: 15 + -15 = 0 0 + -0.6n = 6 + -15 -0.6n = 6 + -15 Combine like terms: 6 + -15 = -9 -0.6n = -9 Divide each side by '-0.6'. n = 15 Simplifying n = 15
| 4(6z-1)-2(z+6)=9(z+1) | | 7p^2-54p-16=0 | | 7x+y=-28 | | 9x^3+6x^2-6x-2=0 | | 5(3x+2)-2=4(4x-30) | | 2+7(x-5)=9-7(x-5) | | 3(6x+2)=9(2x-2) | | -a/6-(31)=64 | | Z^2-2z+11=0 | | 5x^5+9x^3-x+1=0 | | 9=4g-3 | | 12y-8y=32 | | 5x^2-269=51 | | 13+2.50h=11+3.75h | | (s+4)(s-3)=0 | | 4x+5x+9=16 | | 232=75-w | | Log(9)(x^2-6)=Log(9)(30) | | c=108x^2+108xy^2 | | -7-2x=-4 | | 4k(k+5)=0 | | 19-4j=11 | | 14=8+3k | | 5*x^3-3*x^2+8=0 | | 2r(r-4)=0 | | 12-4x-9-3x= | | 3/4x-1/2=181/4 | | 2-4x-9-3x= | | 5*x^3-3*x^2-8=0 | | 4x-5(2x-9)=6(x+5)+3 | | 10+3h=19 | | c=(6x+6y^2)18x |